2014
DOI: 10.1027/0227-5910/a000242
|View full text |Cite
|
Sign up to set email alerts
|

Facing a Patient Who Seeks Help After a Suicide Attempt

Abstract: Specific training is fundamental. Experiential and active methodologies should be used and technical, relational, and emotional questions must be included in the training syllabus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 43 publications
6
40
0
3
Order By: Relevance
“…The attitudes of health professionals seem to significantly affect, whether positively or negatively, the care provided to suicidal patients. However, knowledge of these issues remains unclear (Kelly, McCarthy, & Sahm, ; Rothes, Henriques, Leal, & Lemos, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attitudes of health professionals seem to significantly affect, whether positively or negatively, the care provided to suicidal patients. However, knowledge of these issues remains unclear (Kelly, McCarthy, & Sahm, ; Rothes, Henriques, Leal, & Lemos, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, knowledge of these issues remains unclear (Kelly, McCarthy, & Sahm, 2014;Rothes, Henriques, Leal, & Lemos, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our findings suggest that individuals with no experience of receiving specialized suicide‐prevention training and those with no experience of working with suicidal patients were more affected by the training program than individuals with such experience. A previous study reported that health professionals with no experience of receiving specific training about suicide and those with few experiences of patient suicide attempts exhibited technical and emotional difficulties when treating suicidal patients . This suggests that individuals with experience of suicide‐prevention training or working with a suicidal patient or their family retain a positive attitude and self‐efficacy toward suicide prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Dies scheint v. a. der geringeren Erfahrung im Umgang mit suizidalen Patient/innen geschuldet zu sein. In diesem Sinne zeigte sich, dass der Zusammenhang zwischen dem beruflichen Status und suizidbezogenen Therapeut/innenängsten zumindest partiell durch die Erfahrung im Umgang mit suizidalen Pa tient/ innen vermittelt wurde: Je häufiger bereits mit suizidalen Patient/ innen gearbeitet wurde, umso geringer die Ängste [1,12,13]. Dabei ist jedoch zu beachten, dass der Effekt des direkten Einflusses des Status auf die Ängste größer ist als der indirekte Effekt vermittelt über die Erfahrungen.…”
Section: Diskussionunclassified
“…Therapeut/innen seltener. In einer portugiesischen Befragungsstudie zeigte sich ein vergleichbares Muster [13]: Behandler/innen, die häufiger mit Suizidversuchen von Patient/innen konfrontiert waren ( ≥ 9 Suizidversuche), berichteten weniger technische und emotio nale Schwierigkeiten im Umgang mit suizidalen Patient/innen als solche, die bislang erst selten mit Suizidversuchen konfrontiert waren. Technische Schwierigkeiten beziehen sich hierbei auf fehlendes Interventionswissen zum Umgang mit suizidalen Patient/ innen, während emotionale Schwierigkeiten sich darauf beziehen, dass Ängste vor einem Patient/innensuizid bestehen, man sich gestresst und gestört durch den Patienten fühlt und immer wieder über diesen nachdenkt.…”
Section: Introductionunclassified